BBM - um Processador de Blocos Básicos - Fernandes, Edil S. T.; Silva, Gabriel P. (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2000: Anais do I Workshop em Sistemas Computacionais de Alto DesempenhoDO - 10.5753/wscad_estendido.2000.19135, 2000)
This work presents BBM - a machine oriented towards the execution of basic blocks. Instead of an instruction, the BBM standard unit of processing is the basic block. Many facts regarding the instruction usage of ordinary programs remained unknown for several decades because the traditional processing model, which treats a single instruction as the standard unit, is unable to detect what is happening whith the whole program. With a basic block machine it is possible to have a better insight about the behaviour of the programs. For example, through the experiments involving the execution of the SPECint95 suite on BBM, we found that a very large number of instructions remains unused during the whole execution: in the majority of the programs more than 50% of the instructions remained unused. Disclosed by our Basic Block Machine, this object programs characteristic has many implications on the organization and performance of future processors. Instruction caches and fill units would be much more efficient if the task of mapping instructions onto caches takes in to account the usage and frontiers of the basic blocks. The paper gives an overview of the execution model of our Basic Block Machine, describes the BBM support system, and presents the main results of our experiments.